2014
DOI: 10.1016/j.ijid.2014.03.1387
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cag genotypes of Helicobacter pylori in the esophageal mucosa of dyspeptic patients and its relation to histopathological outcomes

Abstract: H. pylori may coexist in similar proportions without dominance of one cag genotype, suggesting a heterogeneous distribution in the esophagus. The cagE and virB11 genes can be used as markers of cag-PAI in the esophagus. The single cag-PAI genotype in both mucosae confers an increased risk of developing histological damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Subjects were selected from those having matching H. pylori-positive cultures of biopsies of both gastric and esophageal mucosae from a previous study (8 out of 80 dyspeptic patients) taken at the gastroenterology unit of the Oncology Service Hospital of Instituto Venezolano de los Seguros Sociales (IVSS). 5,6 All volunteers signed an informed consent form in accordance with the bioethics committees of Instituto Venezolano de Investigaciones Científicas (IVIC) and IVSS. During endoscopy procedure, antral and esophageal biopsy specimens were collected and submitted for H. pylori culture as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were selected from those having matching H. pylori-positive cultures of biopsies of both gastric and esophageal mucosae from a previous study (8 out of 80 dyspeptic patients) taken at the gastroenterology unit of the Oncology Service Hospital of Instituto Venezolano de los Seguros Sociales (IVSS). 5,6 All volunteers signed an informed consent form in accordance with the bioethics committees of Instituto Venezolano de Investigaciones Científicas (IVIC) and IVSS. During endoscopy procedure, antral and esophageal biopsy specimens were collected and submitted for H. pylori culture as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 In Venezuela, high prevalence of H. pylori in the esophagus (86%) and a heterogenous distribution of cag-pathogenicity island (cag-PAI) genotypes have been demonstrated, indicating the coexistence of different strains in a single host. 4,5 Reports provided by our research group demonstrated multiple H. pylori colonization in the esophageal mucosa by studying cag-PAI genotypes and antibiotic resistance profiles. Helicobacter pylori in the esophageal mucosa was characterized by a partial cag-PAI island and low antibiotic resistance, whereas a higher antibiotic resistance and a complete island were found in the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori has a variable antimicrobial sensitivity pattern, depending on the geographical area and the occurrence of H. pylori resistance that reduces the success of first line treatment. Many studies have been reported on H. pylori isolates from different parts of the worlds, including Germany [ 14 ], India [ 15 ], Brazil [ 16 , 17 ], Venezuela [ 18 ], Chile [ 19 ], Colombia [ 20 ], Iran [ 21 ], Indonesia [ 22 ], and Pakistan [ 23 ]. In Arabian isolates, limited reports have been published on the antimicrobial resistance and virulence factors of H. pylori in UAE [ 24 ] and Kuwait [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…pylori possess many virulence genes; one of them is cag pathogenicity island (cagPAI) (1). CagPAI is since its discovery the most analysed base pairs region of H. pylori chromosome and contains around 30 genes divided into region I and II.…”
mentioning
confidence: 99%
“…Some authors correlate intact cagPAI with severe gastroduodenal diseases, with higher grade of chronic gastritis and premalignant lesions of gastric mucosa. (1,(3)(4), while partially deleated and deleated cagPAI are associated with milder forms of gastroduodenal disease and lower grade of pathological alternations of gastric mucosa (5-6). On the contrary, some of the authors did not find correlation between cagPAI and gastroduodenal disease (7).…”
mentioning
confidence: 99%